SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PAKET WISATA TRAVELING PADA PT. TRITURA JAYA TRAVEL MENGGUNAKAN METODE FUZZY TSUKAMOTO - Yuda Perwira (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2019)
Tritura Jaya Travel is a company engaged in the field of transportation services. In improving services and developing companies, PT. Tritura Jaya Travel increased ticket sales. Problems arise when many bookings want to become tourists. Moreover, with so many assessment criteria, it adds to the problem and slows down the company's performance in making decisions. The solution to the problems mentioned above is by building a decision support system to assist in determining the right traveling tour package. The method chosen to support the solution to the problem above is Fuzzy Tsukamoto by giving weight to each of the selection criteria. This decision support system shows that with the advancement of science and technology can help companies in making the right choice in accordance with the correct consideration and calculation.